Can working conditions explain the return-to-entrepreneurship puzzle? - Daniel S. J. Lechmann (Journal for Labour Market Research, 2015)
Some influential studies show that many self-employed could apparently achieve higher earnings were they working in paid employment. One potential explanation for this 'return-to-entrepreneurship puzzle', not empirically tested yet, is that entrepreneurship entails non-monetary benefits, such as autonomy, flexibility, and task variety. Using German data and a decomposition analysis, I examine the contribution of these working conditions to the observed earnings differential between self-employment and paid employment. I confirm that self-employed individuals report lower earnings than what they are expected to earn in paid employment. However, differences in working conditions barely contribute to the earnings gap. This finding casts some doubt on the relevance of compensating differentials for explaining the return-to-entrepreneurship puzzle.
Keywords: J23; J31; J81; 330; Selbständige; freie Berufe; Einkommenshöhe; abhängig Beschäftigte; erwerbstätige Männer; Arbeitsbedingungen; Einkommenseffekte; Einkommensverzicht; berufliche Autonomie; Arbeitszeitflexibilität; Tätigkeitsmerkmale; Einkommensunterschied; berufliche Selbständigkeit; Arbeitszufriedenheit; Unternehmereinkommen; BIBB/BAuA-Erhebung